Preparasi DNA Spesies Colletotrichum sp. dan Spesifitas Sistem Fingerprinting RAPD - Jamsari, Jamsari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2008)
DNA preparation from C. capsici dan C. gleosporides is important for PCR based analysis of anthracnose causingpathogens. On the other hand, RAPD as one of DNA-based fingerprinting is hindered by its instability and its nonspecifity problems. For that reason, converting RAPD fragments into other DNA based systems is an alternative toincrease its analysis reliability. The study showed that mycelia grown in 2-days liquid culture is appropriate materialfor DNA preparation especially when combined with Shagai-Maroof protocol as well as Promega Genomic DNAIsolation Kit. The study indicated also that some isolated RAPD-fragments showed its instability character. Thiswas proved by the occurrence of multi different length of fragments after re-amplification of some single RAPDspecific fragments.